Are rural and remote patients, families and caregivers needs in life‐limiting illness different from those of urban dwellers? A narrative synthesis of the evidence. (5th July 2016) - Kirby, Sue; Barlow, Veronica; Saurman, Emily; Lyle, David; Passey, Megan; Currow, David
Abstract: This review aimed to assess the evidence to answer the question whether palliative end‐of‐life care needs of patients and caregivers in rural and remote communities differs from those of urban dwellers. Peer‐reviewed studies from 1996 to the present dealing with the experience of rural and remote patients and caregivers at the end‐of‐life compared with that of urban people were extracted for narrative synthesis. The eight studies included showed that palliative needs of rural and remote residents are related to context. Diagnosis and treatment are less well managed in rural areas. Rural differences include: people are more accepting of death and less likely to intervene to delay death; caregivers tend to be younger and include friends as well as family and local support networks are important. Rural and remote end‐of‐life needs are shaped by reduced access and availability of services which has a negative influence on outcomes. This is counterbalanced by an acceptance of death and local support networks. Well‐designed longitudinal studies with samples comprised of rural and urban residents for comparison are required to monitor how end‐of‐life need might change with the approach of death. Clinicians, health services and policy makers need a better understanding of rural attitudes and of how rural community networks mobilise to support end‐of‐life care in their rural and remote communities.